Estimation of stature from percutaneous length of tibia amongst Bengali population - Ghosh, Tapas; Konar, Sudipto (International Journal of Research in Medical Sciences, 2019)
Background: Stature of an individual can be estimated from long bones as these have a direct correlation to the height of an individual. The standing height is mostly contributed lower limb length. Hence regression equations which are best upon length of lower limb long bones are indicative very much. Secular differences of tibial length could be the reason for need of more accurate equation of stature estimation among Bengali population. Methods: In this present study the maximum percutaneous tibial length and the corresponding standing height of adult 260 male and 210 female Bengali subjects were taken. The data were analyzed by parametric statistics and the regression equations were derived. Results: The mean standing height of subjects was 159.15 cm in males and 157.12 cm. in females. It was determined that percutaneous tibial length and stature were positively correlated; the formulated regression equations were seen to be statistically significant (p <0.05) in both the sexes. Conclusions: The present study revealed that there is high degree of correlation between percutaneous tibial length and standing height of Bengali subjects. Hence applicability of the present equations is critically discussed as these will be very much useful for various practical aspects.